Surgical treatment strategy for recurrent parastomal hernia: Experiences from 17 cases - Luan, Li; Liu, Qiaonan; Cui, Changjin; Cheng, Yugang; Zhang, Guangyong; Li, Bo (Frontiers in Surgery, 2022)
Abstract Purpose This study aimed to investigate the surgical treatment strategy of recurrent parastomal hernia (PH) and show its safety, feasibility, and outcomes at a mid-term follow-up. Methods A total of 17 cases of recurrent PH treated at our hospital between January 2016 and October 2021 were included in this retrospective analysis. Patient characteristics were recorded, and the classification of PH, operative time, intraoperative blood loss, hernia repair techniques, as well as follow-up times were compared and analyzed. Results Altogether, 17 patients with recurrent PH underwent successful hernia repair via surgical treatment at The First Affiliated Hospital of Shandong First Medical University and Shandong University Qilu Hospital. No recurrence or severe complications were noted during follow-ups (mean 32.8±3.77 [range 3–68] months). Conclusions For recurrent PH, selecting a suitable repair approach based on intraperitoneal conditions such as infection, abdominal adhesions, or the length of the bowel loop, can help in achieving better therapeutic results. The lap-redo+Sugarbaker technique is worth recommending when the appropriate conditions are met.